2012
DOI: 10.1111/j.2042-7158.2012.01606.x
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro and in-vivo evaluation of austocystin D liposomes

Abstract: This study indicates that AD-Ls are a potential carrier of AD for the treatment of tumours in the liver, increasing the cure efficiency and decreasing the side effects on other tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, the compound is not commercially available. Austocystin D is an organic heteropentacyclic compound isolated from Aspergillus and Aspergillus ustus and has been identified as a potent cytotoxic agent with in vivo antitumor activity and selectivity for cells expressing the multidrug resistance transporter MDR1, which was a characteristic of ACC as well [ 22 24 ]. Selective cytotoxic action of austocystin D arises from its selective activation by cytochrome P450 (CYP) enzymes in specific cancer cell lines, leading to induction of DNA damage in cells and in vitro [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the compound is not commercially available. Austocystin D is an organic heteropentacyclic compound isolated from Aspergillus and Aspergillus ustus and has been identified as a potent cytotoxic agent with in vivo antitumor activity and selectivity for cells expressing the multidrug resistance transporter MDR1, which was a characteristic of ACC as well [ 22 24 ]. Selective cytotoxic action of austocystin D arises from its selective activation by cytochrome P450 (CYP) enzymes in specific cancer cell lines, leading to induction of DNA damage in cells and in vitro [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isotype antibodies were purchased from BD Biosciences (San Jose, CA, USA). Human colon carcinoma Caco-2 cell line (passages [20][21][22][23][24][25][26][27][28][29][30] and human Burkitt's lymphoma Raji B line (passages [30][31][32][33][34][35][36][37][38][39][40] were purchased from American Type Culture Collection (ATCC) (Manassas, VA, USA) and used within the passage mentioned in the parentheses. EFV drug powder and all other chemicals were obtained from Sigma-Aldrich Co.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…It is reported that the dialysis bag may limit the in vitro drug release. 37 Although there is a drug release delay and about 15% of drug remained in the dialysis bag from this in vitro method, this dose decrease will not affect the administrated drug for the future in vitro and in vivo application. Even considering this delay impact from dialysis bag, the dissolution profile for our Pluronic nanodrug formulation is still adequate for sustained drug release requirement.…”
mentioning
confidence: 97%
“…The OD was monitored using ELISA reader at 570 nm. Cell viability percentage and IC 50 (50% inhibitory concentration of cell growth in comparison to untreated control cells as negative control), 22,23 were determined. All tests were done in triplicate.…”
Section: Cytotoxicity Assessmentmentioning
confidence: 99%
“…It is due to the suitable size of liposomal formulations, type, size of cells, incubation time, and a high tendency between liposome and the cell. 22,[39][40][41][42]…”
Section: Cellular Uptake Studiesmentioning
confidence: 99%